2013
DOI: 10.1091/mbc.e12-09-0648
|View full text |Cite
|
Sign up to set email alerts
|

Crucial function of vertebrate glutaredoxin 3 (PICOT) in iron homeostasis and hemoglobin maturation

Abstract: Vertebrate glutaredoxin 3 (PICOT) is essential for the maturation of the heme cofactor of hemoglobin through its essential functions in iron homeostasis. The data suggest an evolutionarily conserved role of cytosolic monothiol multidomain Grxs in cellular iron metabolism pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
104
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(108 citation statements)
references
References 53 publications
2
104
0
Order By: Relevance
“…through the maturation of most iron-containing proteins (Mühlenhoff et al, 2010;Haunhorst et al, 2013). Accordingly, we showed that AtGRXS17 is able to bind Fe 2 S 2 clusters by in vitro reconstitution experiments and complement the defects in iron-sulfur cluster maturation of the Baker's yeast grx5 strain (Figs.…”
Section: Discussion Physiological Function Of Grxs17 In Relation To Imentioning
confidence: 61%
See 1 more Smart Citation
“…through the maturation of most iron-containing proteins (Mühlenhoff et al, 2010;Haunhorst et al, 2013). Accordingly, we showed that AtGRXS17 is able to bind Fe 2 S 2 clusters by in vitro reconstitution experiments and complement the defects in iron-sulfur cluster maturation of the Baker's yeast grx5 strain (Figs.…”
Section: Discussion Physiological Function Of Grxs17 In Relation To Imentioning
confidence: 61%
“…Those present in mitochondria participate in iron-sulfur cluster assembly, most likely as iron-sulfur transfer proteins from scaffold proteins to acceptor proteins (Rodríguez-Manzaneque et al, 2002;Mühlenhoff et al, 2003;Bandyopadhyay et al, 2008). In addition, nucleocytosolic monothiol GRXs participate in iron sensing and trafficking in Baker's yeast (Saccharomyces cerevisiae) and animals (Ojeda et al, 2006;Pujol-Carrion et al, 2006;Kumánovics et al, 2008;Mühlenhoff et al, 2010;Haunhorst et al, 2013). However, it is not known if GRXs play a role in iron-sulfur cluster assembly or iron sensing in plants.…”
mentioning
confidence: 99%
“…The Fe content is not decreased in these yeast cells, but the Fe is not bioavailable due to deficient Fe delivery to mitochondria. A similar defect in Fe bioavailability was observed in zebrafish (Danio rerio) and HeLa cells when HsGRX3 (or the zebrafish ortholog) was depleted (Mühlenhoff et al, 2010;Haunhorst et al, 2013). In plants, BolA2 does not seem to play a role in Fe homeostasis, and the biological output of the GRXS17-BolA2 interaction remains an unanswered question Roret et al, 2014).…”
Section: Grxs17 Associates With Fe-s Client Proteinsmentioning
confidence: 78%
“…Although human and yeast GRXS17 orthologs are essential for the maturation of cytosolic and nuclear Fe-S proteins (Mühlenhoff et al, 2010;Haunhorst et al, 2013), Arabidopsis GRXS17 has recently been shown to play only a minor role in maintaining the activity of two classes of cytosolic Fe-S enzymes (aconitases and aldehyde oxidases; Knuesting et al, 2015). Nonetheless, we identified another Fe-S enzyme, XDH1, to be associated with GRXS17 (Table I).…”
Section: Metabolic Profiling Of Loss-of-function Grxs17 Plants Pointsmentioning
confidence: 85%
“…Because these proteins are involved in intracellular iron trafficking and iron uptake regulation, they seem to play a more general function and hence are no typical CIA proteins. For instance, these glutaredoxins are also involved in the maturation of di-iron proteins such as ribonucleotide reductase or in heme biosynthesis in erythroid cells (Mühlen-hoff et al 2010;Zhang et al 2011;Haunhorst et al 2013). Failure of the glutaredoxins to participate in these processes or in Fe/S protein biogenesis explains the drastic effect on the viability of cells lacking both proteins.…”
Section: Assembly Of Cytosolic and Nuclear Fe/s Proteins Involves Mitmentioning
confidence: 99%